Pengaruh Beban Kerja dan Motivasi Kerja terhadap Kepuasan Kerja pada Pegawai Fakultas Ilmu Sosial Universitas Negeri Padang - Vivi Andriani; Afriyeni Afriyeni (Lembaga Yasin AlSys, 2025)
Research on job satisfaction has been widely conducted, yet studies that specifically analyze the relationship between workload and work motivation in the context of public university employees remain relatively limited, particularly at the Faculty of Social Sciences, Universitas Negeri Padang. This study aims to analyze the effects of workload and work motivation on the job satisfaction of employees at the Faculty of Social Sciences, Universitas Negeri Padang. A quantitative survey design was employed, involving 36 employees selected using a total sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results show that workload has a negative and significant effect on job satisfaction, whereas work motivation has a positive and significant effect on employees’ job satisfaction. These findings contribute to strengthening organizational behavior theory and broaden understanding of the determinants of job satisfaction in the context of higher education institutions. The study concludes that managing workload proportionally and optimizing motivational factors are key aspects in enhancing employees’ job satisfaction, thereby requiring institutions to implement supportive policies based on reward systems, work facilities, and competency development. Theoretically, this study enriches the human resource management literature, while practically it provides a reference for policymakers in higher education institutions and opens avenues for further research exploring mediating or moderating variables in the relationships among the examined constructs.